Adolescent and young adult women's recommendations for establishing comfort with family planning providers' communication about and assessment for intimate partner violence. (2nd January 2019) - Zelazny, Sarah M; Chang, Judy C; Burke, Jessica G; Hawk, Mary; Miller, Elizabeth
ABSTRACT: Background: Intimate partner violence (IPV) is a serious public health problem that disproportionately affects adolescent women seeking family planning services. Current clinical guidelines recommend routine IPV assessment yet provide limited guidance on how to establish patient comfort in addressing this sensitive issue. Few studies exist describing the perspectives of adolescent female patients who have experienced IPV and their suggestions on how providers should communicate about IPV. Methods: This study is a subset of a larger IPV intervention trial in family planning clinics. For this study, we chose a qualitative approach using individual interviews to explore patient perspectives in an open, in-depth manner without limiting potential responses with predetermined answers or investigator-imposed assumptions. We audio recorded clinic encounters for participating providers and patients and interviewed patient participants, asking them to listen to and reflect on how their provider talked about IPV in their audio-recorded clinic encounters. Results: The mean age for the 44 participants was 22.8 years old. Participants named 'comfort' as a main component for discussing and disclosing IPV in the clinical setting. The sub-themes associated with how to create patient comfort include: build the patient-provider relationship, provider should communicate like a friend/be on the patient's level, patient needs to feel cared for by provider, and appropriate timing and space. Conclusion: Methods for establishing patient comfort via communication should be incorporated into and examined within sensitive healthcare areas such as IPV and can be extended to HIV, palliative, and oncological care to improve patient health outcomes.